Price as an Intervening Variable in the Effect of Brand Image on Purchasing Decisions: Study on iPhone Product in The City of Bandung - Meirissa Purwandani; Arry Widodo (Jurnal Manajemen Bisnis, 2022)
This research is to determine the effect of brand image on purchasing decisions with price as an intervening variable on iPhone products in the city of Bandung. The research population is people in the city of Bandung who use iPhone products and require 100 respondents. Descriptive analysis and Structural Equation Model with SmartPLS are the research techniques. The result, brand image has a positive and significant effect on prices, brand image has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions and brand image has a positive and significant effect on purchasing decisions with price as an intervening variable on iPhone products in Bandung.